PENGARUH PERSEPSI MAHASISWA PROGRAM STUDI PENDIDIKAN BAHASA DAN SASTRA INDONESIA TENTANG KOMPETENSI PEDAGOGIK GURU TERHADAP HASIL BELAJAR EVALUASI PEMBELAJARAN - Kumala Dewi, Putri; Warsiman; Hardinata, Vanda (BASTRA : Jurnal Penelitian Pendidikan Bahasa dan Sastra, 2016)
This research is conducted to determine (1) the perception of Diksasindo students towards the learning evaluation competence, (2) the students’ learning outcomes in the BSI Learning Evaluation subject, and (3) whether there is influence between students’ perceptions towards learning outcomes of BSI Learning Evaluation subject or not. This study uses a quantitative approach which employs expost facto typical research. The population and the sample are 71 students. There are some types of data, the first is the perception of students and the second is students’ final grades in the BSI Learning Evaluation subject. Data analysis is conducted by testing the validity and reliability of the questionnaire, the percentage descriptive analysis, normality test, linearity test, simple linear regression test, and hypothesis test with significance level linearity test, t-test, and the determination test (R2). Results shows that 63% of students have good perceptionstowards learning evaluation competence. Furthermore, 49% of students learning outcomes are in the very good category. Simple linear regression result analysis shows regression line equation Y = 53.325 + (0.342) X. This is reinforced with a coefficient linearity significance test results of 0.000 <0.005. It indicates thatthe Diksasindo students have positive perceptions about pedagogical evaluation of learning by 0.342, the study results will also rise by 0.342. The results of the t-test shows a significance coefficient value 0,000 <0,050. It implies that there is influence between students’ perceptions Diksasindo about pedagogical competences of teachers and the learning outcomes of Learning Evaluation. Moreover the determination amount of (R2) is 0.200, it signifies the amount of influence students perceptions on teachers pedagogical competences towards learning outcomes of learning evaluation is 20%, while 80% are influenced by other factors. Concisely, it is suggested for the future researchers to conduct further research in determining other factors by using different research methods.